Awareness Mahasiswa Akuntansi Pada Konvergensi International Financial Reporting Standards (IFRS) Di Provinsi Bali - Putri, Tania Magetsu; Ariyanto, Dodik (E-Jurnal Akuntansi, 2019)
This study aims to provide and empirical awareness of accounting students that is measured by the level of interest, knowledge, challenges, and benefits in influencing IFRS convergence. This research was conducted at six universities in Bali Province and in Higher Education and Private Universities in the VIII Conference area and have an active Bachelor of Accounting program, accounting students. Methods of data collection were conducted by survey method using questionnaire. Data analysis technique used is the Analysis of Multiple Linear Regression. The final result of the study states that the variable level of interest, knowledge, and benefits has a positive effect on awareness of IFRS convergence. While the level of challenge variable has a negative effect  towards IFRS convergence awareness. Keywords :  Interest level, knowledge level, challenge level, benefit level, awareness of IFRS convergence.